Advances in accelerators and medical physics - Nishio, Teiji; Sato, Kiyokazu; Shirai, Toshiyuki (Academic Press, 2023)
"Radiotherapy is now one of the major cancer treatments. The field of accelerator and medical physics is important and growing to support high precision cancer radiotherapy. Advances in Accelerators and Medical Physics provides in-depth and comprehensive coverage of the basic concepts in x-ray therapy, electron beam therapy, particle therapy, boron neutron capture therapy, and molecular imaging and therapy. Novel technologies such as FLASH therapy and laser ion accelerator are also introduced. Each section of the book presents the current state of accelerators, irradiation methods and therapy technologies, as well as future trends in advanced research. This book will serve as a key resource for researchers and students to find all information on latest cancer radiotherapy technologies and methods."